IMPROVING STUDENT ACADEMIC RESILIENCE AT SMAN X SURABAYA - Fikri Hadyan Kusuma; Cholicul Hadi; Maria Eko Sulistyowati (Jurnal Layanan Masyarakat (Journal of Public Services), 2023)
Increasing academic resilience is very important because resilience is how individual go through challenges and face difficult experiences. Students who have high academic resilience are those who remain motivated for academic achievement and high academic performance even though they are faced with stressful situations and conditions that threaten their performance. The aim of this community service is to increase the academic resilience of SMAN X Surabaya students by providing materials and sharing. The method used to increase the academic resilience of SMAN X students is by providing material and sharing. Students of SMAN X were assessed for their academic resilience before and after giving material and sharing to find out changes in students' academic resilience scores. After pre-test, students were given the material about academic resilience, and at the end of it, students were asked to form a group that’s been determined and with one facilitator in each group that will guide them. In that group students were asked to share their experiences in dealing with challenging situations they’ve been through. Each group then summarize what they’ve learned from the story of every student within the group, after that each group then asked to present what they’ve learned within their group to the class. The participants were 34 students of SMAN X Surabaya. Results of test shows there was an increase in the academic resilience score from the average score before providing material and sharing of 112 to 116. These results mean that providing material and sharing increased the academic resilience of students at SMAN X Surabaya. the students were more likely to seek help, closer to their classmates, and more calm when faced with problem.